From Stars to Stones: The Cultural and Linguistic Roots of the Name ‘Skardu’ - Muhammad Nazir; Sajjad Hussain (University of Chitral Journal of Linguistics and Literature, 2024)
The study of toponymy or place names tenders a rare insight into a region’s historical, cultural, and linguistic heritage. The current research explores the etymology of the name Skardu, a city in Pakistan's Baltistan region. Historical evidences show that the name Skardu is a blend of elements from local culture and exotic influence, and linguistically it is rooted in Balti, an old Tibetan dialect spoken in the Baltistan region. Drawing from linguistic analysis and historical texts the current study examines the origin of the name Skardu from the Tibetan word Skar-mDo, usually referred to as a star-lit fort /valley or starry place. Celestial or cosmic reference in the name is a recount and admiration of the earlier Balti settlers for the starry sky and its high altitude symbolizing it with a welcoming sign for the new settlers. In addition, the study found an influence of linguistic variations on the name, for instance, the form Iskardo for Skardu reveals the Islamic influence and a linguistic shift in the region transforming the form and pronunciation of the name. Thus, this study helps to understand the role of religious, linguistic, environmental, and cultural factors in the evolution of toponymic research. Furthermore, it highlights the significance of preserving place names as part of a nation’s intangible heritage.